Investigation of hydrodynamic parameters and separation efficiency of uranium by Tri-n octylamine in a horizontal pulse sieve plate column - H. Badakhshan; A. Gharib; F. Panahinia; M. Ghannadi-Maragheh; J. Safdari; M.H. Mallah (مجله علوم و فنون هسته‌ای, 2020)
In this study, recovery of uranium from leach liquor using solvent extraction technique in a horizontal pulsed sieve plate column was experimentally investigated. Extraction of uranium from an aqueous sulfate solution with 0.25M concentration acid, by using TOA solvent, diluted in kerosene and n-decanol modifier of 5%, 90% and 5% v/v respectively was studied and the influences of operation parameters including the phase flow rates along with pulsation intensity on the dispersed phase holdup, drop size and drop size distribution, as well as extraction efficiency, were evaluated. Increasing pulsation intensity along with the dispersed phase flow rate and decreasing the continuous phase flow rate caused to increase the extraction efficiency. Results showed that the horizontal pulsed sieve plate column has high efficiency for extraction of the uranium from leach liquor. Moreover, a comparative evaluation of available correlations proposed for the prediction of mean drop size and hold up in such columns have been conducted. New correlations for estimating mean drop size and hold up in a horizontal pulsed sieve-plate column were presented, which provided AARE of 7.7% and 8.2%, respectively.